Are language learning strategies motivation-specific? - Mihaljević Djigunović, Jelena (2001)
The results of a study carried out on 362 EFL learners pointed to important connection of motivation with language learning strategies. The connections were found to decrease with incresing age of the learner.
Projekt MZOS
ENG